2010
DOI: 10.1021/ma102164c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Alkyl Side Chains on the Optoelectronic Properties of a Series of Photovoltaic Low-Band-Gap Copolymers

Abstract: The design of novel low-band-gap conjugated polymers with appropriate frontier orbital energy levels and good charge transport is needed to improve the conversion efficiency of organic photovoltaic devices. In this article, we describe the synthesis and structure−property relationships of a series of photovoltaic copolymers with a common conjugated backbone and differing solubilizing side chains. The copolymer optoelectronic properties and the related photovoltaic device performances are reported. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 24 publications
3
78
0
1
Order By: Relevance
“…The PBDT-DTBT series demonstrates that the optimum location for side chains should cause the least steric disturbance to the planarity of the polymer backbone. [ 84,85 ] In this series, PBDT-4DTBT, which is alkylated at the four-position of the thienyl groups, exhibited the highest effi ciency in its BHJ solar cells (Table 7 ). Similar to the control polymer Table 7.…”
Section: Nonaromatic Side Chainsmentioning
confidence: 96%
“…The PBDT-DTBT series demonstrates that the optimum location for side chains should cause the least steric disturbance to the planarity of the polymer backbone. [ 84,85 ] In this series, PBDT-4DTBT, which is alkylated at the four-position of the thienyl groups, exhibited the highest effi ciency in its BHJ solar cells (Table 7 ). Similar to the control polymer Table 7.…”
Section: Nonaromatic Side Chainsmentioning
confidence: 96%
“…Likewise, Heiser recently reported that branched side chains appear to inhibit intercalation in PTBzT 2 blends (based on optimization of power conversion effi ciencies). [ 44 ] PTBzT 2 -β is identical to PBTTT-C12 except for the addition of a benzothiadiazole group between the two unfused thiophene rings, so it is not surprising for fullerene intercalation to occur in PTBzT 2 -α and PTBzT 2 -β .The fact that branched side chains appear to inhibit intercalation in both PBTTT and PTBzT 2 may have implications for the highest performing polymers, since many of them contain branched side chains. [45][46][47][48][49][50] Still, it remains unclear how side-chain branching affects molecular mixing in amorphous domains.…”
Section: Full Papermentioning
confidence: 99%
“…이러한 효율은 기존 실리콘태양전지에 비해 매우 낮은 수준이며 상업적으로 성공하 기 위해선 최소 10%대 이상의 효율을 나타내어야 하는 것으로 보고되고 있다 [8][9][10][11]. 이에 따라 높은 광전변환효율과 안정성 을 확보하기 위해 전자주개 물질로 공액 고분자와 전자받개 물질로 fullerene의 유도체인 PCBM을 혼합한 이종접합형태 (bulkheterojunction, BHJ)구조에 대한 개발이 활발히 진행 중이 며, 8-10%대의 고효율의 구조도 보고되고 있다 [12][13][14].…”
Section: 현재 상용화 되어 있는 P3ht (Poly[3-hexylthiophene])는 4-5%unclassified